2018
DOI: 10.1177/1947603518756462
|View full text |Cite
|
Sign up to set email alerts
|

Treating Severe Knee Osteoarthritis with Combination of Intra-Osseous and Intra-Articular Infiltrations of Platelet-Rich Plasma: An Observational Study

Abstract: Objective Assessing the therapeutic effects of a combination of intra-articular and intra-osseous infiltrations of platelet-rich plasma (PRP) to treat severe knee osteoarthritis (KOA) using intra-articular injections of PRP as the control group. Design In this observational study, 60 patients suffering from severe KOA were treated with intra-articular infiltrations of PRP (IA group) or with a combination of intra-osseous and intra-articular infiltrations of PRP (IO group). Both groups were matched for sex, age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 59 publications
2
90
0
Order By: Relevance
“…We identified four prospective studies 11,49,57,58 and two retrospective studies. 6,9 Their methodological quality was assessed by the level of evidence using the criteria by Wright et al 62 and Slobogean and Bhandari 63 as shown in ►Table 1.…”
Section: Article Identification and Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified four prospective studies 11,49,57,58 and two retrospective studies. 6,9 Their methodological quality was assessed by the level of evidence using the criteria by Wright et al 62 and Slobogean and Bhandari 63 as shown in ►Table 1.…”
Section: Article Identification and Selectionmentioning
confidence: 99%
“…11 The remaining studies had a prospective design and appraised the application of intraarticular and intraosseous injections of PRP in patients with knee OA. The studies by Su et al, 58 Sánchez et al 2018, 57 and Sánchez et al 2016 49 were graded as levels II-IV of evidence, respectively. We limited our analysis of these studies to the patients from the subchondral intraosseous injection group (group A) from the study by Su et al, 58 as well as those from the subchondral intraosseous injection group from Sánchez et al 2018.…”
Section: Article Identification and Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a 2018 observational study by Sánchez et al, they compared IA PRP alone versus IO + IA PRP for severe knee OA in 60 patients. At 2, 6, and 12 months after treatment, the IO + IA group had a significant improvement in all KOOS and WOMAC subscales ( p < 0.05), while the IA group did not improve in any of the scores . Finally, in 2018, Su et al compared IA PRP, IA + IO PRP, and IA hyaluronic acid injections and found the combination of IA + IO PRP resulted in sustained lower VAS and WOMAC scores and improvement in the quality of life at 18 months.…”
Section: Discussionmentioning
confidence: 99%